Smart cities research in Portugal and Spain: An exploratory biliometric analysis - Dias, Gonçalo Paiva (2018)
In this paper it is presented a bibliometric analysis on smart cities research in Portugal and Spain performed using the Scopus® database as a source. Number of articles, citations to those articles, types of sources, most productive and impacting authors and institutions, most cited articles and more relevant subject areas are analyzed and discussed. It is concluded that there is a significant gap between Portugal and Spain in terms of the impact of the research produced, partially explained with the subjects addressed and type of publications used. The results presented here can be of use to researchers and policy makers in the field of Smart Cities’ research mainly as a basis for benchmarking.